Production and characteristics of the exocellular polysaccharide in mutant strains of Xanthomonas fuscans - Konícek, J; Lasík, J; Wurst, M (Folia microbiologica, 1977)
Production of the exocellular polysaccharide of the phytopathogenic bacterium Xanthomonas fuscans was investigated with respect to its possible use in utilization of industrial wastes containing lactose. Six stable lac+ mutants were obtained after the treatment with N-methyl-N-nitroso-N'-nitroguanidine. The mutants were compared with the parent strain. Morphological and cultivation characteristics, as well as production of the exocellular polysaccharide were compared. The production was found to be maximal during the stationary phase of growth in strains cultivated under submerged conditions. Gas chromatography revealed that the polysaccharide of the parent strain is formed by alpha- and beta-D-glucose and alpha- and beta-D-mannose with a small amount of D-ribose and 6-deoxy-L-mannose. Composition of the polysaccharides produced by the mutant strains (lac+) does not qualitatively differ from that of the parent strain. However, they were found to contain a higher quantity of D-mannose, which is favourable for their industrial utilization.
Keywords: Ribose; druhová specificita; Glucose; Methylnitronitrosoguanidine; laktosa; mutace; ribosa; Lactose; Xanthomonas; methylnitronitrosoguanidin; Rhamnose; bakteriální polysacharidy; rhamnosa; Mannose; Galactose; glukosa; Mutagens; Species Specificity; mutageny; stereoizomerie; mannosa; Polysaccharides, Bacterial; Mutation; galaktosa; Stereoisomerism